Cancer and IgE Introducing the Concept of AllergoOncology - Penichet, Manuel L.; Jensen-Jarolim, Erika; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2010)
Allergies are caused by a person$1 (Bs own IgE antibodies directed against innocuous antigens like pollen or house dust mites. Interestingly, several studies have examined the relation between allergies or level of IgE and malignancies and have found an inverse association suggesting a natural role of IgE in cancer immunosurveillance. Is it thus possible that IgE immunoglobulins could have a beneficial function against cancer besides their harmful function in allergy? If so, can we exploit this beneficial function for the development of new cancer therapies? Could oncologists learn from allergists and vice versa? This book attempts to explore step by step these interesting questions, opening a novel science field: AllergoOncology. AllergoOncology by definition aims to reveal the function of IgE-mediated immune responses against cancer cells in order to enhance the understanding of its biology and to develop novel IgE-based treatment options against malignant diseases. Cancer and IgE: Introducing the Concept of AllergoOncology opens new avenues towards IgE antibodies as key effector molecules able to confer protection against cancer development and progression. This affinity-matured class of antibody, belonging to Th2-mediated immunity, uses an exquisite panel of potent effector cells which can eradicate malignant cells. Importantly, IgE is also capable of binding to professional antigen presenting cells thereby enhancing the presentation of cancer antigens and leading to a significant anti-tumor immune response. Based on its anti-tumor efficacy, which has been shown in vitro and in preclinical models, IgE can be potentially used in human in the context passive and active cancer immunotherapy. In summary, this book, which is the first of its class, is a comprehensive volume about the evolving new field AllergoOncology.s
The Biology of IgE: Molecular Mechanism Restraining Potentially Dangerous High Serum IgE Titres In Vivo -- The Biology of IgE: The Generation of High-Affinity IgE Antibodies -- Epidemiological Evidence: IgE, Atopy, and Solid Tumors -- Epidemiological Evidence: IgE, Allergies, and Hematopoietic Malignancies -- Mast Cells in Allergy and Tumor Disease -- The IgE Antibody and Its Use in Cancer Immunotherapy -- IgE Interacts with Potent Effector Cells Against Tumors: ADCC and ADCP -- IgE as Adjuvant in Tumor Vaccination -- The Targets of IgE: Allergen-Associated and Tumor-Associated Molecular Patterns -- The Role of Th2-Mediated Anti-Tumor Immunity in Tumor Surveillance and Clearance.
Keywords: Medicine; Oncology; Immunology; Biomedicine; Cancer Research; Immunology; Oncology